The Many Faces of Information Disclosure - Boot, Arnoud W. A.; Thakor, Anjan V. (Review of Financial Studies, 2001)
In this article we ask: what kind of information and how much of it should firms voluntarily disclose? Three types of disclosures are considered. One is information that complements the information available only to informed investors (to-be-processed complementary information). The second is information that is orthogonal to that which any investor can acquire and thus complements the information available to all investors (preprocessed complementary information). And the third is information that substitutes for the information of the informed investors in that it reveals to all what was previously known only by the informed (substitute information). Our main results are as follows. First, in equilibrium, all types of firms voluntarily disclose all three types of information. Second, in contrast to the existing literature, complementary information disclosure by firms strengthens investors’ private incentives to acquire information. Substitute information disclosure weakens private information acquisition incentives. Third, while complementary information disclosure has an ambiguous effect on financial innovation incentives, substitute information disclosure weakens those incentives.